Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 5 - Section 5.4 - Polynomials in Several Variables - Exercise Set: 5

Answer

$-6$

Work Step by Step

Substituting $x=2$ and $y=-3$, the given expression, $ 2x^2y-5y+3 ,$ evaluates to \begin{array}{l}\require{cancel} 2(2)^2(-3)-5(-3)+3 \\\\= 2(4)(-3)-(-15)+3 \\\\= -24+15+3 \\\\= -9+3 \\\\= -6 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.